The Impact of the United States’s Presence on Chinese Influence in Africa (2000-2022) - Al-Nabet, Mesallam bin Talib bin Aqeel (Dirasat: Human and Social Sciences, 2025)
Objectives: This research aimed to explore the dynamic interplay between American and Chinese influence in Africa from 2000 to 2022, focusing on how U.S. presence impacts China's strategic positioning in the continent. The study also investigates the following pivotal question: In what ways does American presence affect Chinese influence in Africa during this period? The hypothesis posits that a heightened American presence inversely affects Chinese influence. This analysis stands out for its rigorous quantitative approach to U.S.-China competition in Africa, a perspective often overlooked in previous research. Methods: This study used and employed a mixed-methods approach, combining quantitative data analysis with comparative case studies to examine the impact of US’ presence on Chinese influence in Africa (2000-2022). Results: The study results showed that increased American engagement prompts China to bolster its influence aggressively to safeguard its political and economic interests. Furthermore, the research highlights the United States’ acute awareness of the implications of Chinese influence, as it poses a potential threat to American interests. Conclusion: The study shows that the competition between the two powers is marked by convergent strategies, with China leveraging soft power as a counterbalance to the US’ military assertiveness on the continent.